Agent-Based Model of Navigable Inland Waterway Tow Operation Procedures - Nelson, Katherine S.; Camp, Janey V.; Philip, Craig E.; Abkowitz, Mark D. (My University, 2017)
Transportation modeling within the context of extreme weather events induced by climate change is critical to understand and improve the resilience of transport systems as the world moves further into the 21st century. Among transportation modes, navigable inland waterways in particular face severe challenges to their future reliability as a result of extreme weather events. The economic implications of inland waterway operational efficiencies on commercial shipping have been studied in detail for several decades. Less well understood, however, are the effects of tow operation procedures enacted during adverse river conditions that have resulted from extreme weather events. This paper describes a model of a waterway segment that simulates stakeholder decision making and tow operator behavior to provide stakeholders with insights into the possible benefits of waterway action plans as operational guidance documents. Simulations run for a test area of the navigable inland waterway system indicated that operational procedures recommended in waterway action plans might have a significant impact on waterway operational efficiencies, which suggests that the model may be a useful decision-support tool for waterway stakeholders.